Examining information needs of public data service users: a study based on the ‘Message Board for Leaders of People’s Daily in China’ - Xiaoyue Zhang; Jinya Liu; Xinyue Wang; Wanteng Ma; Pu Yan (Information Research: An International Electronic Journal)
Introduction. Governance process optimisation is critical to achieve the goal of improving public services efficiency. Public data service  is crucial starting point for realising this goal. However, practical challenges persist in public data service, including unclear processes and insufficient identification of public data service citizens’ information needs.